2017
DOI: 10.1021/acsnano.7b04981
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Crack Healing in Nanostructured Silica-Based Thin Films

Abstract: Self-healing materials that can spontaneously repair damage under mild conditions are desirable in many applications. Significant progress has recently been made in the design of polymer materials capable of healing cracks at the molecular scale using reversible bonds; however, such a self-healing mechanism has rarely been applied to rigid inorganic materials. Here, we demonstrate the self-healing ability of lamellar silica-based thin films formed by self-assembly of silica precursors and quaternary ammonium-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Interestingly, CT3G30 possesses a high self‐healing efficiency of 82.6%, which could be attributed to the abundant hydrogen bonds within CT3G30 that can easily break and reform, and the SiOSi bonds that possess good chain mobility and high reversibility. [ 19 ] To validate the self‐healing capability, a CT3G30 hydrogel with a blue dye additive and another colorless CT3G30 hydrogel were connected together. After standing for 2 h, the two parts were merged together without any crevice between them, as shown in the inset of Figure 2h.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, CT3G30 possesses a high self‐healing efficiency of 82.6%, which could be attributed to the abundant hydrogen bonds within CT3G30 that can easily break and reform, and the SiOSi bonds that possess good chain mobility and high reversibility. [ 19 ] To validate the self‐healing capability, a CT3G30 hydrogel with a blue dye additive and another colorless CT3G30 hydrogel were connected together. After standing for 2 h, the two parts were merged together without any crevice between them, as shown in the inset of Figure 2h.…”
Section: Figurementioning
confidence: 99%
“…The surfactant-directed self-assembly has been extensively employed to prepare mesoporous bridged silsesquioxane, the so-called periodic mesoporous organosilica, whereas there have been only a few reports on lamellar thin films . We have found that several types of cracks that are barely healed in the conventional lamellar silica films can be readily healed in the lamellar bridged silsesquioxane films even under moderate humidity conditions (50–60% RH at room temperature) (Figure b). Furthermore, enhancements of the hardness and adhesion to the substrate, with retention of the self-healing ability, were achieved by incorporating a newly designed precursor with long bridging organic groups for interlayer cross-linking.…”
Section: Introductionmentioning
confidence: 93%
“…For self-healing of more rigid, highly cross-linked siloxane networks such as silica (SiO 2 ) and silsesquioxane (RSiO 1.5 , where R represents organic groups), one promising approach is to control the nanostructure. Recently, we reported the crack-healing ability of lamellar-structured thin films consisting of nanometer-thick silica layers and cationic surfactant (didodecyldimethylammonium bromide; DDAB) assemblies. , Crack closure was induced by lamella swelling on increasing the humidity, and then rearrangement of the siloxane networks appeared to occur between the closed fracture surfaces . However, there was a limitation in the crack-healing ability; only narrow cracks propagated from large scratches were healed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several works have realized the stiff and healable polymer systems via boroxine bonds [22,25], metal-ligand interactions [26,27], dynamic vinylogous urethane [28], dense hydrogen bonds [23] and Diels-Alder (DA) reactions [29]. Si-O exchange in siloxanes and silyl ethers have been employed to prepare dynamic cross-linked and self-healing Polydimethylsiloxane (PDMS) networks [30][31][32][33][34][35][36][37], rigid vitrimers [38][39][40][41], and recyclable thermoset plastics [42][43][44] as well as self-healing composites [45][46][47]. Therefore, it is important to take advantage of Si-OR and Si-OSi dynamic covalent bonds to explore healable polymers with a general strategy, high mechanical strength, mild healing conditions, recycling abilities and low cost.…”
Section: Introductionmentioning
confidence: 99%